THE IDEAL FORMAT FOR THE IMPLEMENTATION OF ISLAMIC DA'WAH TO STRENGTHEN THE ENFORCEMENT OF ISLAMIC SHARIA IN ACEH (A STUDY OF THE VIEWS OF DAYAH ISLAMIC SCHOLARS) - Teuku Zulkhairi Hamzah (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri (UIN) Ar-Raniry, 2020)
This paper explores the views of dayah scholars towards the ideal format of the implementation of Da'wah Islamiyah in order to strengthen the enforcement of Islamic Sharia in Aceh. The implementation of Islamic Sharia which has been running for a dozen years is need to be supported by the massive implementation of Da'wah Islamiyah because the da'wah calls on people to do what is right and leave evil. To achieve this goal, the implementation of da'wah must be in accordance with the advice of Islam itself, both the delivery method, material, criteria for preaching and the involvement of various elements to ensure the successful implementation of da'wah. This research takes a study of the views of the dayah scholars because it considers that the scholars are a very influential element in Acehnese society. The method of writing this article uses a qualitative approach. Data was collected through in-depth interviews with a number of dayah scholars and preachers in Aceh. The results of this study describe the responses and views of Islamic dayah scholars in Aceh to the methods and strategies of Da'wah Islamiyah that can be used in order to strengthen the enforcement of Islamic Sharia in Aceh. The results of this study can be useful for the formulation of policies of the Aceh government, especially in compiling policies on the implementation of Da'wah Islamiyah so that the process of implementing the Islamic Shari'ah that is running can reach the goals that are aspired. Keywords : Islamic Shari'ah, Da'wah Islamiyah, ulama dayah